A triple-wideband bandpass filter with controllable bandwidths based on stub-loaded resonators. Issue 8 (18th June 2018) - Gong, Li; Xiong, Yang; Zhang, Fan; Wang, LiTian; Sun, Yan; Zhao, XinJie; He, Ming; Ji, Lu; Zhang, Xu; Zhang, Bo
Abstract: In this paper, a triple-wideband bandpass filter (BPF) with controllable bandwidths based on two multi-mode stub-loaded resonators (MMSLRs) and a triple-mode resonator is presented. The MMSLR is loaded with two identical folded open-ended stubs and a T-shaped stub. Each passband of the tri-band BPF is formed by four resonant modes, which provide sufficient bandwidths to meet various application requirement. By adjusting the lengths of open-ended stubs, three passband bandwidths can be controlled individually. The center frequencies of the triple-wideband BPF are allocated at 2.7, 3.67, and 5.44 GHz, with the 3 dB fractional bandwidths (FBWs) of 20.1, 14.7, and 26.3%. Among the three passbands, the highest one covers the 5 G WiFi band (5.15–5.85 GHz). The measured results of the proposed filter exhibit excellent agreement with simulated results.